Electrochemical detection method for doxorubicin concentration in body fluid

By using the CU-CO dual-metal Prussian blue derivatives with carbon-nitrogen space in electrochemical testing, combined with nano-impact electrochemical technology, the detection limit of high detection is high and low in existing electrochemical detection methods. The problem achieves the electrochemical detection effect of high sensitivity and low detection limits.

CN119355095APending Publication Date: 2025-01-24CHONGQING UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411289684.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing electrochemical detection methods are used to detect doxorubicin concentration in body fluids, which have problems such as high detection limit, low sensitivity, and weak electrochemical signal.

Method used

A gold electrode modified with Cu-Co bimetallic Prussian blue derivative Cu-Co PBA-VCN with carbon and nitrogen vacancies was used as the working electrode. Combined with nano-impact electrochemical technology, the amplified electrochemical signal was obtained by chronoamperometry.

Benefits of technology

Electrochemical testing of low detection limit, wide detection range, high sensitivity and high reliability, the detection limit is 17.2nm, and the sensitivity is 61.562 μA/μm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355095A_ABST
    Figure CN119355095A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical detection method for doxorubicin concentration in body fluid, which adopts a Cu-Co bimetallic Prussian blue derivative Cu-Co PBA-VCN modified gold electrode with carbon and nitrogen vacancies as a working electrode, a silver / silver chloride electrode as a reference electrode and a platinum wire as a counter electrode, and the doxorubicin titer is detected through cyclic voltammetry. And nano impact electrochemistry is utilized, and amplified electrochemical signals are obtained through a chronoamperometry. The preparation method of the working electrode comprises the following steps: (1) dissolving sodium citrate and copper nitrate in deionized water, stirring, dropwise adding a K3Co (CN) 6 solution, standing the solution for 24 hours, collecting precipitate, and drying to obtain a Cu-Co PBA precursor; (2) activating the Cu-Co PBA precursor by using H2 plasma, so as to obtain Cu-Co PBA-VCN; (3) adding the Cu-Co PBA-VCN and the MWCNTs into the deionized water, and carrying out ultrasonic dispersion; and (4) dropping the dispersion liquid onto a gold electrode, and drying at 4 DEG C to obtain the working electrode. The detection method has the advantages of low detection limit, wide detection range, high sensitivity, high reliability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical detection, in particular to an electrochemical detection method for doxorubicin concentration in body fluids. Background Art

[0002] Adriamycin, also known as doxorubicin (DOX), is a first-line chemotherapy drug and has been widely used in the treatment of broad-spectrum cancers. However, it also has serious side effects on the human body, and the concentration in the patient's body fluids is highly correlated with the side effects. Therefore, sensitive and reliable detection of DOX concentration in the body during chemotherapy to guide medication is of great significance for improving efficacy and reducing side effects. Existing DOX detection technologies mainly include Raman spectroscopy, liquid chromatography, capillary electrophoresis, fluorescence spectroscopy and electrochemical methods. The key indicators for measuring detection effects include: detection limit, sensitivity, detection range and stability.

[0003] Existing literature N. Thakur, V. Sharma, T.A. Singh, A. Pabbathi, J. Das, Fabrication of novel carbon dots / cerium oxide nanocomposites for highly sensitive electrochemical detection of doxorubicin, Diamond and Related Materials, 125 (2022) 109037. discloses a method for detecting the anticancer drug doxorubicin (DOX) by electrochemical method by modifying screen-printed carbon electrode SPCE (CDs / CeO2 / SPCE) using carbon dots / cerium oxide (CDs / CeO2) nanocomposites. The synthesized CDs / CeO2 nanocomposites are ultrasonically dispersed in acetone to prepare a suspension of nanomaterials. The suspension is dripped onto the surface of SPCE and dried, and the modified SPCE obtained is named CDs / CeO2 / SPCE. The electrode manufacturing process in this method is relatively complicated, and it is not easy to succeed and takes a long time to manufacture; moreover, the detection limit of this detection method is high, the linear range of detection is narrow, the detection electrical signal is weak, and the detection sensitivity is low. The document S. Deepa, BEK Swamy, KVPai, A surfactant SDS modified carbon paste electrode as an enhanced and effective electrochemical sensor for the determination of doxorubicin and dacarbazine its applications: Avoltammetric study, Journal of Electroanalytical Chemistry, 879 (2020) 114748. discloses a technique of fixing an enhancer sodium dodecyl sulfate (SDS) on a carbon paste electrode (MCPE) and using an electrochemical method to detect doxorubicin (DOX). This detection method also has the problems of high detection limit, narrow linear range of detection, weak detection electrical signal and low detection sensitivity. Summary of the invention

[0004] In view of the problems of high detection limit, low sensitivity, weak electrochemical signal and the like of existing DOX electrochemical sensors, the present invention provides an electrochemical detection method for doxorubicin concentration in body fluids. The method accurately detects DOX based on nano-impact electrochemical amplification of DOX electrochemical detection signals, with low detection limit and high sensitivity.

[0005] In the electrochemical detection method for doxorubicin concentration in body fluid provided by the present invention, a Cu-Co bimetallic Prussian blue derivative Cu-Co PBA-V having carbon-nitrogen vacancies is used. CN The modified gold electrode (AuE) was used as the working electrode, the silver / silver chloride (Ag / AgCl) electrode was used as the reference electrode, and the platinum (Pt) was used as the counter electrode to detect the doxorubicin (DOX) titer by cyclic voltammetry; and the amplified electrochemical signal was obtained by chronoamperometry using nano-impact electrochemistry (NIE). The supporting electrolyte used was a 0.1M PBS solution with a pH of 5.0.

[0006] The preparation method of the working electrode is as follows:

[0007] (1) Sodium citrate and copper nitrate were dissolved in deionized water, and K3Co(CN)6 solution was added dropwise after stirring for 30 minutes to obtain a blue solution. The blue solution was allowed to stand at room temperature for 24 hours, and the blue precipitate was collected by centrifugation, washed with water for three times, and dried at 70°C overnight to obtain a Cu-Co PBA precursor.

[0008] (2) The Cu-Co PBA precursor was activated by H2 plasma to obtain a Cu-Co bimetallic Prussian blue derivative Cu-Co PBA-V with carbon and nitrogen vacancies. CN .

[0009] (3) Cu-Co PBA-V CN The multi-walled carbon nanotubes (MWCNTs) are added into deionized water, and dispersed by ultrasonic treatment to obtain a dispersion liquid; wherein the multi-walled carbon nanotubes are mainly used as a dispersant.

[0010] (4) The dispersion was dropped onto the pre-cleaned gold electrode and dried at 4°C to obtain the working electrode Cu-CoPBA-V CN -MWCNTs / AuE.

[0011] The pre-cleaning treatment method of the gold electrode AuE is: polishing the gold electrode AuE on a polishing pad with 20nm alumina slurry, and then ultrasonically cleaning it in deionized water, ethanol and deionized water in sequence, each time for 180 seconds, and then taking out the gold electrode AuE and letting it dry naturally.

[0012] Preferably, in step (1), the molar ratio of sodium citrate, copper nitrate and K3Co(CN)6 is 5:3:2.

[0013] Preferably, in step (2), the conditions for H2 plasma activation treatment are: H2 plasma activation at 0.1 MPa and 200 W power for 40 minutes.

[0014] Preferably, the working electrode is Cu-Co PBA-VCN The content is 5mg.

[0015] Compared with the prior art, the present invention is beneficial in that:

[0016] (1) This method uses H2 cold plasma treatment to prepare Cu-Co bimetallic Prussian blue derivatives with CN vacancies (Cu-Co PBA-V CN ) is used as one of the working electrode materials of the detection device;

[0017] (2) This method uses the direct electrooxidation of DOX in nano-impact electrochemistry as a signal transduction mechanism. CN -DOX on MWCNTs directly impacted the gold electrode, achieving stable signal amplification, and proposed a practical and simple method for amplified electrochemical detection.

[0018] (3) This detection method has the advantages of low detection limit, high sensitivity, wide detection range and high reliability; the linear detection range is 0.05-0.45μM (R 2 =0.9938), 0.5-4.5 μM (R 2 =0.9963) and 5-45 μM (R 2 =0.9920), the sensitivity was 61.562μA / μM, and the detection limit was 17.2nM.

[0019] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention provides a flow chart of the electrochemical detection method for doxorubicin concentration in body fluids.

[0021] Figure 2 Cu-Co PBA precursor and Cu-Co PBA-V after plasma treatment CN XRD pattern of .

[0022] Figure 3 Cu-Co PBA precursor and Cu-Co PBA-V CN TEM images and element distribution maps of Cu-Co PBA. (a) is the TEM image and element distribution map of Cu-Co PBA; (b) is the TEM image and element distribution map of Cu-Co PBA-V CN TEM images and element distribution maps.

[0023] Figure 4 Cu-Co PBA-V with different contents CNThe relationship between the working electrode and the detection peak current.

[0024] Figure 5 This is a graph showing the relationship between supporting electrolytes of different pH values ​​and the magnitude of the detected peak current.

[0025] Figure 6 The signal amplification principle and effect diagram based on nano-impact electrochemistry. (a), (b), and (c) are transient current signal diagrams at different voltages tested using chronoamperometry, and (d) is a schematic diagram of the signal amplification principle based on nano-impact electrochemistry.

[0026] Figure 7 The working electrode is Cu-Co PBA-V CN -MWCNTs / AuE sensitivity test results for DOX detection. (a) is the CV detection curve corresponding to different concentrations of DOX, and (b) is the relationship between peak current and DOX concentration.

[0027] Figure 8 The working electrode is Cu-Co PBA-V CN -MWCNTs / AuE stability and repeatability test results. Among them, (a) is Cu-Co PBA-V CN -MWCNTs / AuE in the presence of 500μM DOX after 50 cycles of continuous scanning CVs. (b) is Cu-Co PBA-V CN -MWCNTs / AuE in the presence of 500 μm DOX was measured for 5 times in parallel. (c) is the stability result of the sensor.

[0028] Fig. 9 LOD radar diagram of different types of materials for DOX electrochemical detection. The numbers in the figure represent different materials: 1 is VMSF / ErGO; 2 is Pt / MWCNTs; 3 is mSiO2@MWCNTs; 4 is AuNPs@COFs-MWCNTs; 5 is Cu-Co PBA-V prepared by the present invention CN -MWCNTs; 6 is rGO / Au / PPY; 7 is L-GSH / MoS2 / CYS; 8 is MB@MWCNTs / UiO-66-NH2; 9 is CDs / CeO2; 10 is AgNPs / MWCNTs;

[0029] 11 is Fe2O3 / MWCNTs; 12 is AuDE / SAM / rGO / Fe2Ni@Au. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] Example 1

[0032] The electrochemical detection method for doxorubicin concentration in body fluid provided by the present invention is as follows: Figure 1 As shown, the specific steps are as follows:

[0033] (1) Preparation of working electrode:

[0034] 1.32 g of sodium citrate and 0.56 g of copper nitrate were dissolved in 100 ml of deionized water, and then stirred continuously at room temperature for 30 minutes. 100 ml of 0.02M K3Co(CN)6 solution was added dropwise to the mixed solution to obtain a blue solution. The blue solution was then allowed to stand at room temperature for 24 hours to precipitate a blue precipitate, which was collected by centrifugation and washed with water three times and dried at 70°C overnight to obtain a Cu-Co PBA precursor. The Cu-Co PBA precursor was activated by H2 plasma at 0.1 MPa and 200 watts for 40 minutes to obtain a Cu-Co PBA-V with carbon and nitrogen vacancies. CN .

[0035] Cu-Co PBA precursor and Cu-Co PBA-V after H2 plasma treatment CN XRD characterization see Figure 2 The XRD patterns show that Cu-Co PBA precursor and Cu-Co PBA-V CN All have the Cu3[Co(CN)6] crystal structure (PDF#21-0875), and the diffraction peaks are consistent with the simulation results (Cu-Co PBA, JCPDS No.51-1895). CN The intensity of the diffraction peak is significantly reduced, which is because the framework of the Cu-Co PBA precursor is damaged to a certain extent after H2 plasma treatment. The above results prove that the Cu-Co PBA precursor and Cu-Co PBA-V CN .

[0036] Cu-Co PBA precursor and Cu-Co PBA-V after H2 plasma treatment CN TEM images and element distribution maps are shown in Figure 3 . (a) is the TEM image and element distribution map of Cu-Co PBA precursor; (b) is the TEM image and element distribution map of Cu-Co PBA-V CN TEM images and element distribution maps. It can be seen that the Cu-Co PBA precursor and Cu-Co PBA-V CNThe materials all have a cubic structure, with sizes of approximately 215 nanometers and 343 nanometers respectively, and contain Co, Cu, N and C elements, which are evenly distributed on the materials. CN The surface is rougher because the Cu-Co PBA precursor framework is damaged to some extent after H2 plasma treatment. These results further prove that the Cu-Co PBA precursor and Cu-Co PBA-V CN Successful preparation.

[0037] The prepared Cu-Co PBA-V CN Add MWCNTs to deionized water and ultrasonically treat for 180 seconds to obtain a dispersion. The unmodified gold electrode AuE was polished with 20nm alumina slurry on a polishing pad, and then ultrasonically treated in deionized water, ethanol and deionized water in turn, each time for 180 seconds. Then take out the AuE and let it air dry naturally. The electrode was modified by the drip method. Before dripping, the prepared dispersion was ultrasonically treated for 180 seconds. Subsequently, 10μL of the dispersion was dropped onto the pre-cleaned AuE and then dried at 4°C to obtain the working electrode Cu-Co PBA-V CN -MWCNTs / AuE.

[0038] (2) The prepared working electrode, a silver / silver chloride (Ag / AgCl) electrode as a reference electrode, and a platinum (Pt) wire as a counter electrode were used to form a three-electrode system. The DOX titer was detected by an electrochemical method, namely, cyclic voltammetry (CV), and the amplified electrochemical signal was obtained by chronoamperometry using nano-impact electrochemistry (NIE).

[0039] (3) Optimize the conditions for electrochemical detection of DOX. Figure 4 and Figure 5 As shown, the Cu-Co PBA-V CN The content of Cu-Co PBA-V and the pH of the supporting electrolyte (0.1M PBS) were optimized. CN The relationship between the working electrode content and the detection peak current size. The larger the peak current, the more obvious the detection signal and the better the detection effect. The best Cu-Co PBA-V CN The content is 5 mg. According to the relationship between the supporting electrolyte with different pH and the detection peak current, the optimal pH of PBS is 5.0.

[0040] (4) The DOX detection electrical signal was amplified using nano-impact electrochemistry. The nano-impact electrochemical experiment was carried out in PBS (0.1 M, pH 5.0) containing 500 μM DOX. The principle of signal amplification based on nano-impact electrochemistry is as follows: Figure 6As shown in (d), DOX is adsorbed on Cu-Co PBA-V CN -MWCNTs and then hit the gold electrode (AuE), converting the oxidation of DOX into an electrical signal. Since it reduces the limit of signal acquisition to the level of a single particle and allows fast response and high-throughput detection of analytes, rich amplified signals are obtained. The transient current in the range of 0.2V to 0.6V was tested by chronoamperometry, and the results are shown in Figure 6 (a), (b), (c) Figures. Figure 6 (a) shows that an electrochemical signal with a period of about 0.4 seconds was obtained at 0.2V. Figure 6 (c) shows that at 0.23 V, a special set of amplified signals is obtained, consisting of a weak signal and a series of strong signals. The period of this set of signals is about 2.4 seconds, and the maximum current is 1.46 times the minimum current. These amplified signals help achieve low detection limits, high sensitivity, and high reliability for electrochemical detection of DOX.

[0041] (5) Under optimized detection conditions, the electrode Cu-Co PBA-V CN -MWCNTs / AuE sensitivity to DOX detection. The experiment was carried out in 0.1M PBS (pH 5.0), and the CV detection curves corresponding to different concentrations of DOX are shown in Figure 7 (a). Figure 7 (b) is the relationship between the peak current and the DOX concentration. It can be seen that in the concentration ranges of 0.05-0.45 μM, 0.5-4.5 μM and 5-45 μM, the peak current is linearly related to the DOX concentration. The corresponding regression equations are I pa =61.562(μM)+180.66(R 2 =0.9938), I pa =7.3473(μM)+211.72(R 2 =0.9963), I pa =0.955(μM)+245.82(R 2 =0.9920). The detection limit was 17.2 nM (S / N=3). Cu-Co PBA-V CN -MWCNTs electrode has a sensitivity of 61.562μA / μM for DOX detection.

[0042] Then, the working electrode Cu-Co PBA-V CN -MWCNTs / AuE stability and reproducibility. In the presence of 500μM DOX, the same Cu-Co PBA-V CN -MWCNTs / AuE was scanned continuously for 50 cycles. Figure 8 As shown in (a), the electrode retains 97.87% of the peak current value of the first cycle, showing excellent stability. Figure 8 (b) Five Cu-Co PBA-V were tested in the presence of 500 μM DOX. CN The reproducibility of the MWCNTs / AuE electrode was estimated to be 0.20% with a relative standard deviation (RSD), indicating good surface reproducibility. The working electrode was stored in a refrigerator at 4 °C for 7 days using the same Cu-Co PBA-V CN -MWCNTs / AuE were tested every other day under 500 μM DOX to evaluate the reproducibility. Figure 8 As shown in (c), the working electrode retained 88.54% of the peak current detected on the first day, indicating excellent reproducibility.

[0043] Fig. 9 It is a LOD radar chart of different types of materials for electrochemical detection of DOX. Obviously, the method of the present invention shows a lower detection limit. Table 1 summarizes the comparison of the effects of different types of materials for electrochemical detection of DOX. It can be further seen that the detection method of the present invention is more sensitive to the detection of DOX, and the electrochemical detection signal is stronger, with a detection limit of 17.2nM, which has obvious advantages in both detection limit and detection range.

[0044] Table 1. Performance comparison between the detection method of the present invention and the DOX electrochemical detection method reported in the literature

[0045]

[0046]

[0047] The names of the references in Table 1 are as follows:

[0048] [1] N. Thakur, V. Sharma, TASingh, A. Pabbathi, J. Das, Fabrication of novelcarbon dots / cerium oxide nanocomposites for highly sensitive electrochemical detection of doxorubicin, Diamond and Related Materials, 125 (2022) 109037.

[0049] [2]R.Hajian,Z.Tayebi,N.Shams,Fabrication of an electrochemical sensorfor determination of doxorubicin in human plasma and its interaction withDNA,J Pharm Anal,7(2017)27-33.

[0050] [3]S.Rong,L.Zou,L.Meng,X.Yang,J.Dai,M.Wu,R.Qiu,Y.Tian,X.Feng,X.Ren,L.Jia,L.Jiang,Y.Hang,H.Ma,H.Pan,Dual function metal-organic frameworks basedratiometric electrochemical sensor for detection of doxorubicin,Anal ChimActa,1196(2022)339545.

[0051] [4]X.R.Lin,Y.F.Zheng,X.C.Song,Electrocatalysis and Detection ofNitrite on a Pd / Fe(2)O(3)Nanocomposite Modified Glassy Carbon Electrode,JNanosci Nanotechnol,18(2018)4858-4864.

[0052] [5]H.Ilkhani,T.Hughes,J.Li,C.J.Zhong,M.Hepel,Nanostructured SERS-electrochemical biosensors for testing of anticancer drug interactions withDNA,Biosens Bioelectron,80(2016)257-264.

[0053] [6]M.Behravan,H.Aghaie,M.Giahi,L.Maleknia,Determination ofdoxorubicin by reduced graphene oxide / gold / polypyrrole modified glassy carbonelectrode:A new preparation strategy,Diamond and Related Materials,117(2021)108478.

[0054] [7]Y.Wan,Y.F.Zheng,H.T.Wan,H.Y.Yin,X.C.Song,A novel electrochemicalsensor based on Ag nanoparticles decorated multi-walled carbon nanotubes forapplied determination of nitrite,Food Control,73(2017)1507-1513.

[0055] [8]S.V.Selvi,A.Prasannan,S.M.Chen,A.Vadivelmurugan,H.C.Tsai,J.Y.Lai,Glutathione and cystamine functionalized MoS(2)core-shell nanoparticles forenhanced electrochemical detection of doxorubicin,Mikrochim Acta,188(2021)35.

[0056] [9]H.Zhao,K.Shi,C.Zhang,J.Ren,M.Cui,N.Li,X.Ji,R.Wang,Spherical COFsdecorated with gold nanoparticles and multiwalled carbon nanotubes as signalamplifier for sensitive electrochemical detection of doxorubicin,Microchemical Journal,182(2022)107865.

[0057] It can be seen from the above experimental test results that the electrochemical detection method for doxorubicin concentration of the present invention achieves comprehensive performance requirements such as low detection limit, wide detection range (linear interval between peak current and DOX concentration), high sensitivity and high reliability.

[0058] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. An electrochemical detection method for doxorubicin concentration in body fluids, characterized in that: Cu-Co bimetallic Prussian blue derivative Cu-Co PBA-V with carbon and nitrogen vacancies CN The modified gold electrode was used as the working electrode, the silver / silver chloride electrode was used as the reference electrode, and the platinum wire was used as the counter electrode to detect the doxorubicin titer by cyclic voltammetry; and nano-impact electrochemistry was used to obtain the amplified electrochemical signal by chronoamperometry.

2. The electrochemical detection method for doxorubicin concentration in body fluids according to claim 1, characterized in that: The preparation method of the working electrode is as follows: (1) Sodium citrate and copper nitrate were dissolved in deionized water, and K3Co(CN)6 solution was added dropwise after stirring for 30 minutes to obtain a blue solution, and the blue solution was allowed to stand at room temperature for 24 hours, and the blue precipitate was collected by centrifugation and dried to obtain a Cu-Co PBA precursor; (2) The Cu-Co PBA precursor was activated by H2 plasma to obtain a Cu-Co bimetallic Prussian blue derivative Cu-Co PBA-V with carbon and nitrogen vacancies. CN ; (3) Cu-Co PBA-V CN and MWCNTs were added into deionized water and dispersed by ultrasonic treatment to obtain a dispersion; (4) The dispersion was dropped onto the pre-cleaned gold electrode AuE and dried at 4°C to obtain the working electrode Cu-CoPBA-V CN -MWCNTs / AuE.

3. The electrochemical detection method for doxorubicin concentration in body fluids according to claim 2, characterized in that: In step (1), the molar ratio of sodium citrate, copper nitrate and K3Co(CN)6 is 5:3:

2.

4. The electrochemical detection method for doxorubicin concentration in body fluids according to claim 2, characterized in that: In step (2), the conditions for H2 plasma activation treatment are: H2 plasma activation at 0.1 MPa and 200 W power for 40 minutes.

5. The electrochemical detection method for doxorubicin concentration in body fluids according to claim 2, characterized in that: The working electrode is Cu-Co PBA-V CN The content is 5mg.

6. The electrochemical detection method for doxorubicin concentration in body fluids according to claim 2, characterized in that: The pre-cleaning treatment method of the gold electrode AuE is: polishing the gold electrode AuE on a polishing pad with 20nm alumina slurry, and then ultrasonically cleaning it in deionized water, ethanol and deionized water in sequence, each time for 180 seconds, and then taking out the gold electrode AuE and letting it dry naturally.

7. The electrochemical detection method for doxorubicin concentration in body fluids according to claim 1, characterized in that: The supporting electrolyte used was a 0.1 M PBS solution with a pH of 5.0.